2016
DOI: 10.1177/1073191116680292
|View full text |Cite
|
Sign up to set email alerts
|

Using the Personality Assessment Inventory Antisocial and Borderline Features Scales to Predict Behavior Change: A Multisite Longitudinal Study of Youthful Offenders

Abstract: A substantial amount of research has examined the developmental trajectory of antisocial behavior and, in particular, the relationship between antisocial behavior and maladaptive personality traits. However, research typically has not controlled for previous behavior (e.g., past violence) when examining the utility of personality measures, such as self-report scales of antisocial and borderline traits, in predicting future behavior (e.g., subsequent violence). Examination of the potential interactive effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
2
5
0
Order By: Relevance
“…Our findings add to the extant literature on analysing PAI items to predict a number of patient variables, such as malingering, pathological traits, behaviour change and suicide risk (Aita et al, 2017;Gaines et al, 2013;Penson et al, 2018;Ruiz et al, 2018;Sinclair et al, 2016). Additionally, our present findings expand on findings from our previous work (Cersosimo et al, 2021), which revealed that patients who reported lower early session alliance also reported more ANT; specifically, more antisocial behaviours and therapists reported higher early session alliance with patients who reported more ARD, specifically those with traumatic stress.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Our findings add to the extant literature on analysing PAI items to predict a number of patient variables, such as malingering, pathological traits, behaviour change and suicide risk (Aita et al, 2017;Gaines et al, 2013;Penson et al, 2018;Ruiz et al, 2018;Sinclair et al, 2016). Additionally, our present findings expand on findings from our previous work (Cersosimo et al, 2021), which revealed that patients who reported lower early session alliance also reported more ANT; specifically, more antisocial behaviours and therapists reported higher early session alliance with patients who reported more ARD, specifically those with traumatic stress.…”
Section: Discussionsupporting
confidence: 80%
“…This might potentially aid in evaluating personality pathology across contexts while using an updated diagnostic framework. Penson et al (2018) focused their work on whether antisocial (ANT) and borderline personality disorder (BOR) clinical scales on the PAI could predict future offending behaviour and other negative life outcomes in a multisite study of adolescent offenders (n = 1354).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher scores reflected the greater degree of personality traits. According to Morey [28], several studies have demonstrated the reliability and validity of the PAI subscales in normal, clinical, and student populations [29]. In our study, the internal consistency was excellent for the ASPD features scale (α = .91) and the BPD features scale (α = .90).…”
Section: Measuresupporting
confidence: 64%
“…This result was surprising given that several studies have shown BPD to be a good predictor of reactive aggression [6,7,9]. In a recent longitudinal study, however, Penson et al [29] showed that BPD characteristics were not sufficient in significantly predicting aggressive behaviors and rather, that ASPD characteristics were better predictors. Thus, it is likely that, in our regressions, ASPD traits were more effective predictors of reactive aggression than BPD traits.…”
Section: Discussionmentioning
confidence: 94%